Properties of permeable blocks according to replacement ratio of activated alumina - Yoo, Jaegyun; Lee, Jeongtaek; Jeon, Eunyeong; Lee, Sangsoo (Edelweiss Applied Science and Technology, 2024)
Conventional permeable blocks are subject to efflorescence by acidic water and are unable to maintain consistent water permeability. Accordingly, the object of the present study is to produce permeable blocks using the activated alumina with known anion adsorption properties, determine the performance of such blocks, and examine their functionality and potential for use as building materials. Test results showed that whereas the permeability coefficient and anion adsorption performance tended to improve as the activated alumina replacement rate increased, the strength tended to decrease. It is determined that improvement of the permeability coefficient and adsorption performance owe to the porous nature of the activated alumina.